Odpowiedzi

2009-12-17T18:40:58+01:00
1.
7x+3y=-1 / × 5
2x+5y=14 / × (-3)

35x+15x=-5
-6x-15x=-42

35x=-5
-6x=-42

29x=-47
x=1,62

2.
4(x-2)-y=1
2x-4y=8

4x-8-y=1
2x-4y=8 / × (-2)

4x-8-y=1
-4x+8y=-16

-y=9
8y=-16
y=-2

3.
5x-y=7
2(x+1)=2y

5x-y=7 / × (-2)
2x-2y=-2

-10x+2y=-14
2x-2y=-2

-8x=-16
x=2

4.
4(x-2)-(y-2)=1
10x+2y=18

4x-8+y+2=1 / × (-2)
10x+2y=18

-8x+16-2y-4=-2
10x+2y=18

-8x=-14
10x=18

2x=4
x=2

5.
6x-9y=6
8x+5y=7/3 / × 3

6x-9y=6 / × (-4)
24x+15y=7

-24x+36y=-24
24x+15y=7

51y=17
y=2,29













2009-12-17T18:45:34+01:00
1. 7x+3y=-1 |*2
2x+5y=14 |*(-7)

14x+6y=-2
-14x-35y=-98
---------------
-29y=-100|; (-29)
y=3,45

7x+10,35=-1
y=3,45

x=1,62
y=3,45


2. 4(x-2)-y=1
2x-4y=8

4x-8-y=1
2x-4y=8 |*-2)

4x-y=9
-4x+8y=-16
------------
7y=-7 |:7
y=-1

2x+4=8
y=-1

x=2
y=-1


3.
5x-y=7
2(x+1)=2y

5x-y=7
2x+2=2y

5x-y=7 |*(-2)
2x-2y=-2

-10x+2y=-14
2x-2y=-2
----------------
-8x=-16 |:(-8)
x=2

10-y=7
x=2

-y=-3 |*(-1)
x=2

y=3
x=2



4. 4(x-2)-(y-2)=1
10x+2y=18

4x-8-y+2=1
10x+2y=18

4x-y=7 |*2
10x+2y=18

8x-2y=14
10x+2y=18
--------------
18x=32|:18
x=1,78

4*1,78-y=7
x=1,78

y=-0,12
x=1,78


5.
6x-9y=6
8x+5y=7/3